The impact of attitudes, attachment and partner control on intimate partner violence(IPV): a cross-cultural comparison - Albini, Laura; Browne, Kevin (2018)
Attitudes regarding gender roles and acceptance of violence, attachment style and need for control have been strongly implicated in IPV perpetration. However, arguments have been raised regarding the weight of these variables in relation to IPV. The present online cross-sectional study aimed at comparing these variables’ strength of association between Italian and English participants to better discern attitudinal dispositions. Analyses relied on data from 194 participants collected via an online questionnaire. Logistic regression aimed at predicting IPV indicated parental violence and control as significant contributors to the likelihood of perpetrating IPV, with a moderate to strong influence of attitudes supportive of violence and lack of chivalry, and the implication of fearful attachment style and childhood experiences of violence. Important differences were found on attitude endorsement across nationalities, and on the relationship between fearful attachment and control/violence across gender. These are discussed in relation to risk assessment and interventions.